2021
DOI: 10.1109/access.2021.3067702
|View full text |Cite
|
Sign up to set email alerts
|

Joint Optimization of Computation Offloading, Data Compression, Energy Harvesting, and Application Scenarios in Fog Computing

Abstract: Fog computing is considered to be an effective method to solve the problem of high latency and high energy consumption of IoT devices. A suitable computation offloading strategy can provide a low offloading cost to the user device. Most researches on computation offloading in fog computing focus on one or two targets to improve system performance, however, the actual system needs to meet a comprehensive demand. Therefore, the joint optimization of multi-objective in multiple scenarios is a very meaningful prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…e task offloaded to the fog will be redistributed by the algorithm, and some will be further offloaded to the cloud server. According to [9,11,14,15], it is known that the offloading backhaul data is extremely small, much smaller than of the offloaded, so the return cost is chosen to be ignored. Let the transmission rate between users and F-AP be B F ; then, the transmission time to the fog is…”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…e task offloaded to the fog will be redistributed by the algorithm, and some will be further offloaded to the cloud server. According to [9,11,14,15], it is known that the offloading backhaul data is extremely small, much smaller than of the offloaded, so the return cost is chosen to be ignored. Let the transmission rate between users and F-AP be B F ; then, the transmission time to the fog is…”
Section: Problem Formulationmentioning
confidence: 99%
“…Moreover, the processing speed of the local device, the fog server, and the cloud server is set to f L � 2.1 × 10 8 cycle/s, f F � 5 × 10 9 cycle/s, and f C � 10 × 10 9 cycle/s [9], respectively. e wireless transmission rate between the local and F-AP is 15 Mbps and from the fog to cloud is 40 Mbps [15]. Besides, ϕ � 100cycle/s, T limit � 1200ms, H � 500, and c � 1J/s are further set.…”
Section: Evaluation and Simulationmentioning
confidence: 99%
“…Biswas et al [80] focused on reducing the energy loss problem and designing an energy-efficient data transfer scenario between IoT devices and clouds. Bai et al [81] suggested a joint computation offloading, data compression, energy harvesting, and application scenarios algorithm for FC. Maher et al [82] introduced a data backup system based on multicloud and FC.…”
Section: E Data Utility Based Algorithmsmentioning
confidence: 99%
“…Among these solutions, harvesting energy from RF signals neither demands complex energy harvesting equipments nor depends time-variant energy resources. Such advantages of this energy harvesting solution induce it to become a bright candidate deployed in small-size users in 5G mobile communications or IoT to provision energy, linger the life-time, and enhance energy efficiency [6][7][8]. Currently, this solution can be carried out through SWIPT (simultaneous wireless information and power transfer) [9][10][11] or relaying communications [12][13][14].…”
Section: Introductionmentioning
confidence: 99%